Malignant Colo-Duodenal Fistula: A Case Report and Literature Review (Journal of Chittagong Medical College Teachers' Association, 2010)
Due to errors in this paper, a corrected version is reprinted in Vol.20(2) 2009 p.53-55.Key words: colo-duodenal fistula; malignant; clinical suspicion DOI: 10.3329/jcmcta.v20i1.4940 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):64-67